Human and Angelic Manner - Ali Mohammad Farhadzadeh (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Health is a vital concept in human life and always the Human being shares some aspects of  both animals and angels; while the greatest commonality of  human and animals lies in physical and mundane features, wisdom is what human and angels have in common. For downloading the full-text of this article please click here.